Science games and the development of scientific possible selves - Beier, Margaret (2012)
Serious scientific games, especially those that include a virtual apprenticeship component, provide players with realistic experiences in science. This article discusses how science games can influence learning about science and the development of science-oriented possible selves through repeated practice in professional play and through social influences (e.g., peer groups). We first review the theory of possible selves (Markus and Nurius 1986) and discuss the potential of serious scientific games for influencing the development of scientific possible selves. As part of our review, we present a forensic game that inspired our work. Next we present a measure of scientific possible selves and assess its reliability and validity with a sample of middle-school students (N=374). We conclude by discussing the promise of science games and the development of scientific possible selves on both the individual and group levels as a means of inspiring STEM careers among adolescents.